An action research about the effects of social-emotional learning in a second language acquisition teacher preparation course - Herrera Luis Javier Pentón (Psychology of Language and Communication)
The current action research explored the effects of social-emotional learning (SEL) in an online second language acquisition (SLA) graduate course. Employing the CASEL (2010) framework as the lens, I examined the following research question: What effects does social-emotional learning have on second language teachers in a second language acquisition course? Findings indicated that embedding SEL into the SLA course resulted in participants becoming increasingly self-aware of their learner-selves (i.e., self-awareness), prompting them to deploy a series of strategies to regulate their behaviors and practices as self-taught language learners and teachers (i.e., self-management). Increased empathy and understanding toward their present and future students (i.e., social awareness) was also noted, which contributed to students’ building positive, supportive relationships beyond the online classroom (i.e., relationship skills). Finally, SEL prompted participants to reflect on their identities, ideologies, and privileges as language teachers, learners, and speakers, which resulted in making caring and constructive choices (i.e., responsible decision-making).